2009
DOI: 10.1186/ar2865
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4-Ig interacts with cultured synovial macrophages from rheumatoid arthritis patients and downregulates cytokine production

Abstract: IntroductionCo-stimulatory signal B7(CD80/CD86):CD28 is needed in order to activate T cells in immune response. Cytotoxic T lymphocyte-associated antigen-4-immunoglobulin (CTLA4-Ig) binding to the B7 molecules on antigen-presenting cells downregulates this activation and represents a recent biological treatment in rheumatoid arthritis (RA). Objectives of the study were to investigate the presence of the B7.2 (CD86) molecule and its masking by CTLA4-Ig on cultures of both RA synovial macrophages (RA SM), and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 30 publications
9
40
0
2
Order By: Relevance
“…Abatacept might directly activate certain pathways in macrophages via CD80/86, resulting in the inhibition of cytokine release upon Tck stimulation, as was suggested by Cutolo et al 12. They demonstrated, using a concanavalin-A-activated Jurkat T cell line, that abatacept was capable of reducing the (immunocytochemically) detectable levels of IL-6 and TNFα in RA synovial tissue macrophages, underscoring the clinical relevance of the results described in this paper.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Abatacept might directly activate certain pathways in macrophages via CD80/86, resulting in the inhibition of cytokine release upon Tck stimulation, as was suggested by Cutolo et al 12. They demonstrated, using a concanavalin-A-activated Jurkat T cell line, that abatacept was capable of reducing the (immunocytochemically) detectable levels of IL-6 and TNFα in RA synovial tissue macrophages, underscoring the clinical relevance of the results described in this paper.…”
Section: Discussionsupporting
confidence: 84%
“…Activation of mouse DCs via CD80/86 by CTLA4-expressing T cells resulted in the production of IFNγ by the DCs 11. It was recently suggested that CTLA4-Ig, via a direct effect on macrophages, reduces the ability of macrophages to produce cytokines upon stimulation with concanavalin-A-activated Jurkat T cells 12. We therefore investigated whether abatacept could influence the RA disease course by diminishing the proinflammatory cytokine production by macrophages induced upon contact with cytokine-activated T cells and TLR ligands.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that abatacept might exert alternate modes of action independent from T-cell activation blockade, as it was described in collagen-induced arthritis 26. This might also be consistent with additional effects of abatacept observed on others cell types expressing CD80/CD86 on their surfaces, including B cells27 28 and monocytes 29 30. However, we observed that abatacept failed to protect CB17-SCID mice from the development of bleomycin-induced dermal fibrosis, which strongly supports that T cells directly drive the antifibrotic properties of abatacept in this model.…”
Section: Discussionsupporting
confidence: 83%
“…Si può ipotizzare che il blocco dei recettori B7.1/B7.2 tramite CTLA4-Ig potrebbe altresì esercitare effetti diretti sulle APC, in particolare sui macrofagi che, come noto, giocano un ruolo fondamentale in diverse fasi della sinovite che si accompagna all'AR. Studi in vitro che abbiamo condotto in precedenza hanno dimostrato la presenza della molecola B7.2 sulla superficie di macrofagi sinoviali (MS) ottenuti da pazienti affetti da AR attiva e inoltre hanno evidenziato i possibili effetti anti-infiammatori di CTLA4-Ig in co-colture di MS AR e cellule T attivate (9). Pertanto, in questo lavoro ci proponiamo di valutare i MS come possibili cellule target per il trattamento con CTLA4-Ig, in assenza della popolazione linfocitaria T, analizzando gli effetti di CTLA4-Ig sulla produzione di citochine pro-infiammatorie quali IL-6, TNFalfa e IL-1beta da parte degli stessi MS.…”
Section: Lavoro Originaleunclassified
“…sentate da MS AR sono state incubate per 24 ore in terreno addizionato con CTLA4-Ig alla concentrazione di [500 μg/ml], la concentrazione più significativa usata in base ai risultati ottenuti in precedenti studi farmacologici clinici e sperimentali (9). Il fenotipo dei macrofagi è stato confermato tramite colorazione immunocitochimica con anticorpo HAM56 (Dako, Carpinteria, CA, USA), specifico per cellule macrofagiche umane.…”
Section: Lavoro Originaleunclassified